2021
DOI: 10.3390/ijms22041616
|View full text |Cite
|
Sign up to set email alerts
|

A Human Cellular Model for Colorectal Anastomotic Repair: The Effect of Localization and Transforming Growth Factor-β1 Treatment on Collagen Deposition and Biomarkers

Abstract: Anastomotic leakage (AL) is a devastating complication after colorectal surgery, possibly due to the loss of stabilizing collagen fibers in the submucosa. Our aim was to assess the formation of collagen in the colon versus the rectum with or without transforming growth factor (TGF)-β1 exposure in a human cellular model of colorectal repair. Primary fibroblasts were isolated by an explant procedure from clinically resected tissue rings during anastomosis construction in 19 consecutive colorectal patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Previous studies in NHDFs indicated that IL-6 is anti-proliferative at ≥10 ng/mL while IL-1β (0.1 ng/mL) is proliferative [ 22 ]. In our studies of NHDFs using the BrdU incorporation assay [ 23 , 24 ], IL-6 and IL-1β did not significantly influence DNA synthesis at 30 ng/mL and 1 ng/mL, while IL-6 at 100 ng/mL tended to reduce ( p = 0.052) BrdU incorporation into NHDFs ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous studies in NHDFs indicated that IL-6 is anti-proliferative at ≥10 ng/mL while IL-1β (0.1 ng/mL) is proliferative [ 22 ]. In our studies of NHDFs using the BrdU incorporation assay [ 23 , 24 ], IL-6 and IL-1β did not significantly influence DNA synthesis at 30 ng/mL and 1 ng/mL, while IL-6 at 100 ng/mL tended to reduce ( p = 0.052) BrdU incorporation into NHDFs ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 77%
“…NHDFs were cultured in DMEM with GlutaMAX™, glucose (4.5 g/L) and pyruvate (Gibco, Life Technologies, Grand Island, NY, USA) with 10% fetal bovine serum (FBS; Gibco heat-inactivated qualified FBS, 10500064, Thermo Fisher Scientific, Waltham, MA USA), penicillin (100 IU/mL) and streptomycin (100 μg/mL). Cells were incubated in a humidified atmosphere of 5% CO 2 /air at 37 °C and were passaged using 0.05% trypsin-0.02% EDTA (Biological Industries, Kibbutz Bet-Haemek, Israel) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Promoter agents include FGF, TGF-α and VEGF. Turlu et al showed that TGF-β1 represents a potential therapeutic agent for the prevention of anastomotic leakage by increasing collagen synthesis and collagen deposition 104 . Positive effects also have local factors, such as hypoxia, low pH and high levels of lactic acid 89 .…”
Section: Discussion 8924-109mentioning
confidence: 99%
“…In bladder cancer patients, PD-L1 expression is discordant at metastatic sites and the primary tumor, suggesting the dynamic nature of the ECM ( Mukherji et al, 2016 ). TGF-β has been reported to increase the synthesis and deposition of type I collagen and downregulate MMP-2 ( Türlü et al, 2021 ). Activation of the RhoA/ROCK signaling pathway and transcription of SNAIL1 and TWIST1 genes are both triggered by TGF-β ( Gaggioli et al, 2007 ; García-Palmero et al, 2016 ; Chung et al, 2021 ).…”
Section: Inflammatory Factors On Response To Immune Checkpoint Inhibi...mentioning
confidence: 99%